Getting the Most out of Social Media: What Is Social Media? - Caroline R. Warwick; Lauri M Baker; Jessica C. Fernandez; Joy Rumble (EDIS)
This EDIS publication is written for Florida agriculturalists, Extension agents, agricultural organizations, and other individuals interested in successfully using social media to connect with their stakeholders, potential customers or other individuals. This 3-page publication focuses on describing social media and examples of different social media and each’s use. Minor revision by Caroline R. Warwick, Lauri M. Baker, Jessica C. Fernandez, and Joy N. Rumble.